La tercera orilla. Religion popular y vida urbana - Jesús Galindo Cáceres (Estudios sobre las Culturas Contemporáneas)
Starting from an ethnographic research scheme, there is a proposal for taking description up to the level of organisation of sense; from maps and cartography up to the rules and grammar of social life. Action £ind sense constitute the centre of human life. Social composition is configured at several levels; the most evident one, everyday life, is the lower; the deepest, sense of life, is the higher. Religion is at the higher level, but it affects the whole organisation of social life. Social actors play their roles on two elementary stages, a public and a private one, but there is a third one: that of trascendence, that of sense, that of the contact with nothing else than an invisible point, the third shore.